Molecular analyses in Indonesian individuals with intellectual disability and microcephaly - Farmaditya EP Mundhofir; Rahajeng N Tunjungputri; Willy M Nillesen; Bregje WM van Bon; Martina Ruiterkamp-Versteeg; Tri I Winarni; Ben CJ Hamel; Helger G Yntema; Sultana MH Faradz (Indonesian Pediatric Society Publishing House, 2013)
Background Intellectual disability (ID) often coincides with an abnormal head circumference (HC). Since the HC is a reflection of brain size, abnormalities in HC may be a sign of a brain anomaly. Although microcephaly is often secondary to ID, hereditary (autosomal recessive) forms of primary microcephaly (MCPH) exist that result in ID. Objective To investigate mutations in MCPH genes in patients with ID and microcephaly. Methods From a population of 527 Indonesian individuals with ID, 48 patients with microcephaly (9.1 %) were selected. These patients were previously found to be normal upon conventional karyotyping, fragile X mental retardation 1 (FMRl) gene analysis, subtelomeric deletion, and duplication multiplex ligationdependent probe amplification (MLPA). Sanger sequencing for abnormal spindle-like microcephaly-associated (ASPM) and WD repeat domain 62 (WDR62) was performed in all 48 subjects, while sequencing for microcephalin (MCPHl), cyclin-dependent kinase 5 (CDK5) regulatory subunit-associated protein 2 (CD5KRAP2) , centromere protein} (CENPJ), and SCUfALl interrupting locus (STIL) was conducted in only the subjects with an orbitofrontal cortex (OFC) below -4 SD. Results In all genes investigated, 66 single nucleotide polymorphisms (SNPs) and 15 unclassified variants which were predicted as unlikely to be pathogenic (lN2), were identified. Possible pathogenic variants (lN3) were identified in ASPM. However, since none of the patients harboured compound heterozygous likely pathogenic mutations, no molecular MCPH diagnosis could be established. Interestingly, one of the patients harboured the same variants as her unaffected monozygotic twin sister, indicating that our cohort included a discordant twin. Conclusions This study is the first to investigate for possible genetic causes ofMCPH in the Indonesian population. The absence of causative pathogenic mutations in the MCPH genes tested may originate from several factors. The identification of UV2 and UV3 variants as well as the absence of causative pathogenic mutations calls for further investigations.